Modern operative dentistry : principles for clinical practice - Torres, Carlos Rocha Gomes (Cham : Springer, 2020)
This book provides the theoretical knowledge required by students when learning how to diagnose oral diseases, plan treatment, and perform various types of dental restoration. It is also useful for clinicians wishing to update their treatment skills and broaden their understanding operative dentistry. Adopting an evidence-based approach, and in accordance with the philosophy of minimally invasive dentistry, it explains in detail the use of both classic and new restorative materials in various clinical situations. It also discusses the principles of smile analysis, as well the technique for esthetic composite restorations on posterior and anterior teeth, including direct and indirect veneers. In addition to richly illustrated, step-by-step descriptions of procedures, it offers essential information on basic topics, such as dental instruments and equipment, nomenclature and general principles of tooth preparation, isolation of the operating field, matrix and wedge systems, light curing, and pulpal protection. Furthermore it addresses the diagnosis of dental caries and tooth sensitivity of non-carious origin, like dentin hypersensitivity, dental erosion and cracked tooth syndrome, together with their treatment options. Also explaining the fundamental ergonomic principles of clinical practice, the book enables undergraduate students to embark on a successful professional career.
1. Diagnosis and Treatment Planning.- 2. Ergonomics Principles Applied to the Dental Clinic.- 3. Cariology.- 4. Instruments and Equipments.- 5. Nomenclature and classification of cavities and tooth preparation.- 6. General Principles of Tooth Preparation and Carious Tissue Removal.- 7. Isolation of the Operating Field.- 8. Matrix and Wedge Systems.- 9. Protection of the Dentin-pulp Complex.- 10. Tooth Preparations for Amalgam Restorations.- 11. Amalgam Restorations.- 12. Extensive Amalgam Restorations.- 13. Light-curing units.- 14. Composite restoration on anterior teeth.- 15. Composite restoration on posterior teeth.- 16. Preventive measures and minimally invasive restorative procedures.- 17. Aesthetic veneers -- what are they and how to handle them?.- 18. Dentin hypersensitivity and cracked teeth.
Online resource; title from PDF title page (SpringerLink, viewed January 8, 2019).
Added to collection customer.56279.3
Keywords: Dentistry, Operative; Dentistry, Operative